Bird Stories from Latin America: Lessons on Change and Adaptation - Sault, Nicole (Ethnobiology Letters, 2020)
When people hear bird sounds, they understand them on various levels that are interpreted according to cultural context. Among Indigenous cultures of Latin America, avian voices are understood in relation to group identity, kinship affiliation, and personal experience, such as dreams and vision quests. Birds are recognized as social actors with their own voices that express intentions, desires, needs, and responsibilities. Certain birds may impart messages to specific people, and stories of these personal interactions represent both traditional values as well as individual explanations for what the bird communicated. These experiences are incorporated into the dynamic relationships people have with birds, the ancestors, the landscape, and spirit beings, and assist in addressing both cultural and climatic changes. This essay presents stories from Mexico, Costa Rica, and Peru, and shows how individuals interpret bird communications according to cultural values that relate to their personal situation. These avian messages gain new meaning and urgency during periods of dramatic change, like the current climate crisis. As people seek creative responses to survive, relationships with birds provide resiliency.